Potret dan Dinamika Wirausaha Muda Kreatif Kaliabu - Onto Kusumo; Dewi Cahyani Puspitasari (Jurnal Studi Pemuda, 2017)
This study aimed to understand the emergence of the creative class in the context of youth villager. This study used a case study approach by taking the case of the emergence of graphic designers at Kaliabu Village, Magelang Regency. This study used the theory of Creative Class and Youth to explain the dynamics of the emergence of the creative class in Kaliabu. Opportunities in the form of professional graphic designers who comes in line with the current socio-economic changes currently utilized by the younger generation Kaliabu. These changes are related to the economic system based on information technology, progress and financial services industry, the emergence of the company with a flexible system, global supply chains, as well as the process of globalization. These things are external factors that allow graphic designers in Kaliabu Village to carry out cross-country service transactions in online graphic design marketplaces such as 99design.The external change then responded with passion of high exploration by youths Kaliabu. The success of one of the residents in Kaliabu by winning the online design contest fortunately inspire other youths. The learning process occurs among Kaliabu youth. Ultimately in 2012 in the village of Kaliabu already has two hundred young people who become a graphic designer. They are embodied in a community called as Rewo-Rewo. Their function as provider of graphic design and the relations on aspects of talent, technology, and tolerance explaining they are parts of the creative classes. The conclusion of this study showed that the rise of the creative class in the form of hundreds of graphic designers in Kaliabu is a result of the dynamics of youth Kaliabu in response to socio-economic changes. The graphic design of the logo brought economic benefits to them.